The railway man [videorecording (DVD)] - Firth, Colin, 1960-; Kidman, Nicole, 1967-; Irvine, Jeremy, 1990-; Sanada, Hiroyuki, 1960-; Lomax, Eric (2014)
Based on an autobiography, this film tells the true story of Eric Lomax, a British Army officer who is captured by the Japanese during WWII and sent to a POW camp, where he is tortured and forced to work on the Thai-Burma Railway. Years later, and still suffering the psychological trauma of his wartime experiences, Lomax is persuaded by his wife Patti to find and confront one of his captors. Accompanied by his best friend, Lomax returns to the scene of his torture and manages to track down his captor, Japanese officer Takashi Nagase, from the prison camp, in an attempt to let go of a lifetime of bitterness and hate.